Maqasid Al-Shari'ah's Analysis of the Prohibition of Ihtikar In the Perspective of Sharia Economic Law Between the Principles of Benefit and Justice - Siti Mahfuzah; Muhammad Syafiq (Saqifah: Jurnal Hukum Ekonomi Syariah, 2025)
Ihtikar or the practice of hoarding goods with the aim of obtaining excessive profits is one of the actions that is prohibited in Islam. This prohibition is based on the principle of Maqasid al-Shari'ah which aims to realize benefits and justice in economic life. This article analyzes the concept of ihtikar from the perspective of sharia economic law with the Maqasid al-Shari'ah approach to see the extent to which the prohibition contributes to the protection of people's rights and economic stability. The novelty of this research lies in the analytical approach to the prohibition of ihtikar using the framework of Maqasid al-Shari'ah, which has not been explored in depth in the context of sharia economic law in Indonesia. Using a qualitative research method based on literature studies, this study found that ihtikar is contrary to the goals of sharia, especially in the aspects of hifz al-mal (protection of property) and hifz al-nafs (protection of life). The ihtikar ban aims to prevent economic exploitation, create a fairer distribution of wealth, and maintain market balance. In addition, the principle of justice in sharia economic law affirms that every individual has the right to access goods and services at a reasonable price without any adverse monopoly practices. Thus, the prohibition of ihtikar is not only an economic rule, but also an instrument to achieve social welfare and economic justice in an Islamic perspective.